Sistem IoT Berbasis Mikrokontroler Untuk Monitoring Parameter Kualitas Air pada Budidaya Ikan Nila - Hafni; Irwan; Hendry (Jurnal Nasional Teknologi Komputer, 2025)
Water quality is defined as the condition of water assessed and evaluated based on specific parameters and standardized measurement methods. Degraded water quality—such as increased turbidity—can result in reduced dissolved oxygen levels, decreased feeding activity in fish, and obstruction of fish gills by suspended sediment particles. Consequently, water quality serves as a critical factor in aquaculture monitoring, as it directly influences fish growth performance and overall pond productivity. This study aims to develop an integrated water-quality monitoring system for tilapia aquaculture ponds, utilizing a turbidity sensor to detect water clarity and an ultrasonic distance sensor (SRF-05) to measure water level. Both sensors interface with a control unit based on the ATMega328p microcontroller implemented on an Arduino Uno board. The control unit processes sensor data and regulates water conditions through a single relay module connected to two 10W water pumps. The acquired sensor data are transmitted and visualized in real time on an Android application, developed using the Java programming language, to facilitate remote monitoring. The system is expected to support tilapia farmers by providing continuous, accessible, and automated water-quality surveillance, thereby enhancing management efficiency and improving aquaculture outcomes.